Effects of competition, exercise, and mental stress on secretory immunity - Ring, C.; Carroll, D.; Hoving, J.; Ormerod, J.; Harrison, L. K.; Drayson, M. (Journal of Sports Sciences, 2005)
It has been suggested that the psychological stress associated with competitive sports events may help to explain the increased susceptibility to respiratory infections due to reductions in secretory immunity. In the current study, we investigated the influence of competitive exercise and psychological stress on secretory immunoglobulin A (s-IgA). Salivary s-IgA and heart rate were measured in 62 healthy young recreationally active men at rest and, in a between-subjects design, following one of four 8-min tasks: mental arithmetic, cycling at workloads of 60 to 180 W (mean = 146 W), mental arithmetic while cycling, or competitive cycling. Mental arithmetic was associated with significant increases in s-IgA concentration (mean = 49µg· min-1) and s-IgA secretion rate (mean = 25 µg · ml-1) compared with rest, while mental arithmetic combined with exercise was associated with a significant increase in s-IgA concentration only (mean = 124 µg ·min-1). In contrast, competitive exercise and exercise alone did not influence s-IgA concentration or secretion rate. Heart rate increased modestly to mental arithmetic (mean = 7 beats · min-1) and substantially, and similarly, to the three exercise tasks (mean = 56(62 beats · min-1). The hypothesis that the psychological stress of competitive exercise contributes to increased susceptibility to infection via reductions in s-IgA requires further investigation.